New developments in the diagnosis and management of cardiac allograft vasculopathy. - Mehra, M R (1995)
The major cause of late death in cardiac transplant recipients is cardiac allograft vasculopathy, also referred to as cardiac transplant atherosclerosis, which occurs in as many as 45% of transplant recipients who survive longer than 1 year. It differs from typical atherosclerosis in that intimal hyperplasia is concentric and diffuse, the internal elastic lamina remains intact, calcification is rare, and the disease tends to develop rapidly. Intravascular ultrasound and coronary angioscopy are more sensitive diagnostic measures of cardiac allograft vasculopathy than is coronary angiography. Although retransplantation at present seems to be the only definitive therapy for cardiac allograft vasculopathy, it has shown only fair results. Recent studies have suggested that calcium entry blockers and angiotensin-converting enzyme inhibitors may play a beneficial role in delaying the progression of cardiac allograft vasculopathy.